2012
DOI: 10.1016/j.cyto.2012.03.027
|View full text |Cite
|
Sign up to set email alerts
|

Discovering cytokines as targets for chemotherapy-induced painful peripheral neuropathy

Abstract: Chemotherapy-induced peripheral neuropathy (CIPN), a dose-limiting neurotoxic effect of chemotherapy, is the most common reason for patients stopping their treatment early thereby increasing the risk of recurrence and decreased survival rate. Inflammatory cascade activation, proinflammatory cytokine upregulation, and neuro-immune communication play essential roles in the initiation and progression of CIPN. Most notably, TNF-α, IL-1β, IL-6, and CCL2 are involved in neuropathic pain experienced by patients under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
162
0
6

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 179 publications
(172 citation statements)
references
References 85 publications
(112 reference statements)
4
162
0
6
Order By: Relevance
“…T cells and macrophages infiltrate damaged neuronal tissue, and neuroimmune-mediated mechanisms may play a role in disease progression (34,35). Although the tissue target of RgIA4 is unknown, it is noteworthy that the parent compound, RgIA, reduces neural immune cell accumulation (T cells, macrophages, and acetylcholine-synthesizing lymphocytes) after CCI (9,13).…”
Section: Discussionmentioning
confidence: 99%
“…T cells and macrophages infiltrate damaged neuronal tissue, and neuroimmune-mediated mechanisms may play a role in disease progression (34,35). Although the tissue target of RgIA4 is unknown, it is noteworthy that the parent compound, RgIA, reduces neural immune cell accumulation (T cells, macrophages, and acetylcholine-synthesizing lymphocytes) after CCI (9,13).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the TRPV1-mediated anti-cancer effects of cannabidiol have been reported in multiple cancer cell lines, including breast [118], lung [119,120], and colon [121]. Inflammatory and neuro-immune responses also play important roles in the development and progression of CIPN [122]. Phytotherapies, especially cannabinoids, have significant anti-inflammatory and immunomodulatory properties [123].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Yan and Weng (22) recently reported that IL-1␤ generated in the spinal cord of neuropathic rats contributes to central sensitization; the activity of presynaptic NMDA receptors is enhanced by activation of the sphingomyelinase/ceramide signaling pathway that results in increased glutamate release from the primary afferent terminals. Whereas the underlying causative mechanisms of CIPN following paclitaxel are multifactorial and include neuropathological changes in the periphery (23), prominent neuropathological changes in the CNS have been documented to contribute through the development of neuroinflammation and dysregulation of neuroglia communication in the spinal cord (24). We hypothesize that if paclitaxel-induced neuropathic pain is dependent on the activation of the S1P/S1PR 1 axis, then anti-S1PR 1 -targeted approaches should provide an effective means to mitigate CIPN without interfering with anticancer effects.…”
mentioning
confidence: 99%